Impact of religious fasting on resting blood pressure and hydrogen sulfide bioavailability in high-normal blood pressure population / Syahirah Amirah Syaharudin ... [et al.]. - Syaharudin, Syahirah Amirah; Linoby, Adam; Mohd Dan, Azwa Suraya; Abdul Sattar, Munavvar Zubaid; Ghazali, Ahmad Nizal; Ishii, Isao (2024)
Hydrogen sulfide (H2S) has emerged as a critical gasotransmitter with significant roles in blood pressure (BP) regulation and cardiovascular health. Despite growing evidence from pre-clinical studies highlighting the vasodilatory effects of H2S, its role during fasting in humans remains unexplored. This study tested the hypothesis that religious fasting during Ramadan would reduce resting BP and enhance H2S bioavailability in individuals with high-normal BP. We examined the effects of a month-long fasting regimen on systolic BP and plasma H2S levels in fourteen adult Muslim men with high-normal BP (systolic BP 130-139 mmHg, diastolic BP 85-89 mmHg; mean ± SD: age 32 ± 5 years, body mass 85 ± 4 kg, height 1.7 ± 0.08 m). Baseline tests were conducted before fasting, followed by assessments on Day-1, Day-14, and Day-28 at two fasting durations (5 hours and 10 hours). The results demonstrated a significant reduction in systolic BP at the 10-hour fasting duration on Day-14 (mean decrease of 8.5 ± 3.2 mmHg) and Day-28 (mean decrease of 10.2 ± 3.8 mmHg) compared to baseline (p < 0.05). Additionally, plasma total H2S concentrations increased significantly on Day-7 (mean increase of 15.3 ± 4.1 μM) and Day-28 (mean increase of 17.8 ± 4.5 μM) compared to baseline and Day-1 (p < 0.05). These findings suggest that religious fasting can effectively lower BP and increase H2S bioavailability, providing a non-pharmacological approach to managing BP in high-normal BP populations.